Media image of political leaders of Central Asian countries in global media - Abylkhanova, Ә.; Ashirbekova, Г.Ш. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2024)
examines the fundamental aspects of the representation of political leaders in the media, positioning them as a cornerstone of a country's overall image. Given the role of the president as the primary figure shaping perceptions of the state on the international stage, the study analyzes how their statements and actions influence public opinion both domestically and internationally. The study focuses on Kazakhstan, Uzbekistan, Kyrgyzstan, Tajikistan, and Turkmenistan, considering their historical commonalities, similarities in political trajectories, and the interaction of their leaders with global political figures. The research draws on publications from reputable media outlets covering the activities of these leaders. Special emphasis is placed on examining the personal characteristics of political leaders as an integral component of their media image. International studies highlight a growing trend in public attention toward the personal traits of leaders, which often exert a greater influence on their image than the political events themselves. Through a comparative analysis of domestic and international research, the study identifies a direct correlation between press freedom, the reliability of information, and the construction of a positive media image for political leaders. The article analyzes freedom of the press indices in Central Asian countries and their impact on the nature and content of information, particularly during significant political events.